Identification and characterization of a solute carrier, CIA8, involved in inorganic carbon acclimation in Chlamydomonas reinhardtii - Machingura, Marylou C (J Exp Bot, 2017)
The supply of inorganic carbon (Ci) at the site of fixation by Rubisco is a key parameter for efficient CO(2) fixation in aquatic organisms including the green alga, Chlamydomonas reinhardtii. Chlamydomonas reinhardtii cells, when grown on limiting CO(2), have a CO(2)-concentrating mechanism (CCM) that functions to concentrate CO(2) at the site of Rubisco. Proteins thought to be involved in inorganic carbon uptake have been identified and localized to the plasma membrane or chloroplast envelope. However, current CCM models suggest that additional molecular components are involved in Ci uptake. In this study, the gene Cia8 was identified in an insertional mutagenesis screen and characterized. The protein encoded by Cia8 belongs to the sodium bile acid symporter subfamily. Transcript levels for this gene were significantly up-regulated when the cells were grown on low CO(2). The cia8 mutant exhibited reduced growth and reduced affinity for Ci when grown in limiting CO(2) conditions. Prediction programs localize this protein to the chloroplast. Ci uptake and the photosynthetic rate, particularly at high external pH, were reduced in the mutant. The results are consistent with the model that CIA8 is involved in Ci uptake in C. reinhardtii.